Exploring essentially three-turn courses of action: An institutional case study with implications for ordinary talk - Kevoe-Feldman, Heidi and Robinson, Jeffrey D. (Discourse Studies, 2012)
This article describes an adjacency-pair organized course of action in the institutional context of customers calling an electronics repair facility to request the status of equipment they have previously sent in for repair. Relative to the majority of adjacency-pair sequences described in previous research, this course of action is rare in that it is essentially (vs contingently) composed of three (vs two) turns, including status solicitation, status response, and acceptance/rejection of status response. After defending this finding, we situate and discuss its significance relative to prior research - in both ordinary and institutional contexts - on adjacency-pair sequence organization, including implications for sequence-based relevance rules, such as preference organization. Finally, we outline a possible general explanation for why some initiating actions set in motion essentially three-turn (vs two-turn) courses of action, and offer a candidate example in ordinary conversation.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80MzQ5NjI2OQ